Conversion of Nyamplung Oil into Green Diesel through Catalytic Deoxygenation using NiAg/ZH Catalyst - Isalmi Aziz; Lisa Adhani; Muhammad Ihsan Maulana; Mohammad Ali Marwono; Adid Adep Dwiatmoko; Siti Nurbayti (Jurnal Kimia Valensi, 2022)
Nyamplung oil (Calophyllum inophyllum L) can be converted into green diesel by the catalytic deoxygenation method. Bimetallic catalyst NiAg supported by hierarchical natural zeolite (NiAg/ZH) can be used in this method. This study aims to determine the characteristics of the NiAg/ZH catalyst and the optimal conditions for the catalytic deoxygenation of nyamplung oil into green diesel. The NiAg/ZH catalyst was synthesized by wet impregnation with a total metal concentration of 10% and a mass ratio of Ni/Ag of 4. X-Ray Diffraction, Surface Area Analyzer and NH3-TPD characterized the catalyst. Catalytic deoxygenation of Nyamplung oil was carried out by varying the temperature (325, 350 and 375 °C) and reaction time (1, 2 and 3 hours) with a catalyst dosage of 5%. The composition of the product was analyzed using Gas Chromatography-Mass Spectroscopy. The catalyst XRD spectrum showed a peak at 2θ = 22.38° (clinoptilolite zeolite), 44.42° (Ni) and 38.21° (Ag). The surface area of the catalyst is 46.7024 m2/g, the pore volume is 0.0813 cc/g, the average pore diameter is 6.9632 nm, and the deposit is 1.6882 mmol/g. The optimum catalytic deoxygenation of nyamplung oil was obtained at 350 °C and 3 hours with a gasoline selectivity of 3.51%, kerosene 4.73%, and 62.02% green diesel.